2022
DOI: 10.1177/00031348221083938
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 4D CT Scan in Re-operative Parathyroid Surgery

Abstract: Parathyroidectomy is the only cure for primary hyperparathyroidism and is effective in more than 95% of cases at initial surgical intervention. However, 2.5-5% of cases have recurrent or persistent disease. Pre-operative imaging is recommended in patients undergoing redo parathyroidectomy to localize the diseased gland. Parathyroid 4D CT scan is now widely used for localization and has been reported to have improved accuracy when compared to other imaging modalities. We conducted a retrospective study of all r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…In the management of parathyroid adenoma, 4D CT has emerged as a highly accurate diagnostic tool, with up to 93% correct lateralization in single gland disease and 87% in revision cases. 16,17 Our study found that 4D CT correctly localized adenoma quadrant in around 64% of cases, at a significantly greater rate than USG or SES. This rate is still somewhat lower than in the published literature; however, this is likely due to our institution's protocol of utilizing it as a second-line imaging modality reserved for those that have had unsuccessful first-line imaging modalities.…”
Section: Discussionmentioning
confidence: 56%
“…In the management of parathyroid adenoma, 4D CT has emerged as a highly accurate diagnostic tool, with up to 93% correct lateralization in single gland disease and 87% in revision cases. 16,17 Our study found that 4D CT correctly localized adenoma quadrant in around 64% of cases, at a significantly greater rate than USG or SES. This rate is still somewhat lower than in the published literature; however, this is likely due to our institution's protocol of utilizing it as a second-line imaging modality reserved for those that have had unsuccessful first-line imaging modalities.…”
Section: Discussionmentioning
confidence: 56%
“…While echography has the advantage of being non-expensive and not representing a source of irradiation, other techniques use different radiation doses such as parathyroid scintigraphy and four-dimensional (4D) computed tomography (CT) scans. Also, an enhancement in the baseline features as provided by the neck ultrasound may be provided by 4D MRI (magnetic resonance imaging) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Компьютерная томография с внутривенным болюсным контрастированием по данным литературы обладает чувствительностью от 67 до 89% [43]. По нашим данным ДЧ КТ с внутривенным болюсным контрастированием в группе перед повторной операцией составила 78%, что сопоставимо с данными литературы.…”
unclassified